Bollywood, mobility and partition politics: representation of displaced Muslims in films on Indo-Pak partition - Raj, Sony Jalarajan; Sreekumar, Rohini (My University, 2024)
The ultimate horror of history is not the persistent fear that it is bound to repeat itself but the very unfathomable nature of the temporal and spatial coordinates that constitute its existence as an incomprehensible form of knowledge. The discontinuous and disrupted notion of history is a self-negation of certainty and any opposite activity to place the reality of events in the historical timeline has farreaching consequences. Such a discourse of history is an extension of the violence perpetuated through the fragmented memories of our collective consciousness. India, entwining the webs of its complex and traumatic past, exemplifies this perception of history, not just the narrativization of the past embellished by the ambience of nostalgia but a vortex of uncertainty through which the present finds its meaning. The historical significance of ‘Indianness’ perplexed in the literary and cinematic forms is a product of the ‘historical violence’ that literally erupted from the day when India as a nation came into existence, and is subliminally rerepresented through the spectacles of artistic imaginations. The event known as the Indo-Pak Partition or the independence of India/Pakistan was a ‘seismic political transformation’ conjoining the regional identities into the larger geographical narrative of cinema which mutated the linguistic and cultural elements along the way of emerging migratory patterns (Vasudevan 2010). The epistemological, artistical, ethical, cultural, and political modes of ‘being’ stuck in between the binary border politics emanating from the Partition are precisely historical and this is the vantage point where one must start scrutinizing the inveterate discourses of India.
Keywords: film and television studies; refugee and migration studies; history: 20th century to present; Indo-Pak Partition